Penerapan Metode Dakwah Mau’idzah Hasanah oleh Para Da’i di Media Massa - Yuli Umro'atin Yuli (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
Abstract The success of da'wah is largely determined by how it is carried out. The procedures for preaching, including the packaging of materials, attitudes and ways of delivering da'wah material are more important than the material for da'wah. No matter how perfect the material, the completeness of the material and the actuality of the issues presented, if it is delivered in a careless, unsystematic and haphazard way, it will create an unpleasant impression. But on the other hand, even though the da'wah material is not perfect, the simple material and the issues presented are less actual, but presented in an interesting and evocative way, it will create a happy impression. mau'izhah hasanah means good teaching, or good messages, delivered as advice. The da'wah method is the path used by da'wah interpreters to convey the teachings of Islamic da'wah material. In conveying a message of da'wah, the method plays a very important role, because even though a message is good, it is conveyed through an incorrect method, then the message may be rejected by the recipient of the message. Mau'idzah hasanah is a utterance that contains good advice, where it can be useful for people listening to it, or satisfying arguments so that the audience can justify what is conveyed by the subject.